Cloning Journalism Practices and Violations of Journalistic Ethics (Case Study of Press Company Organizations in Bengkulu Local Media) - Imran, Tri Yulianti; Gushevinalti, Gushevinalti; Marlina, Neneng Cucu (PT FORMOSA CENDEKIA GLOBAL, 2024)
This thesis is entitled